ISLAMIC PERSPECTIVE ON THE USE OF PATHOGEN BACTERIA AS AN ANTIBACTERIAL ETHANOL EXTRACT TEST ACTIVITY OF WHITE PUMPKIN LEAVES (Lagenaria siceraria) - Handayany, Gemy Nastity (Universitas Islam Negeri Alauddin Makassar, 2015)
There had been a research of antibacterial extract of white pumpkin leaves (Lagenaria cineraria) activity towards some pathogen bacteria. The objective of the study was to present the antibacterial activity of extract of white pumpkin leaves, commonly called Lagenaria siceraria, against some 8 pathogen bacteria such as (Escherichia coli, Vibrio sp, Streptococcus mutants, Staphylococcus aureus, Salmonella thypi, Pseudomonas aeroginosa, Bacillus subtilis, and Staphylococcus epidermidis). The research was conducted by extracting the white pumpkin leaves and using 96% ethanol liquid. Afterwards the screening test was performed using microbe test and ethanol extract of white pumpkin leaves with 0,5% concentration and 1 % (b/v) with negative control of disc piper. It was found that the 0,5% concentration could prevent 4 pathogen bacteria such as Escherichia coli, Streptococcus mutants, Staphylococcus aureus, and Staphylococcus epidermidis. After conducting the screening test followed by the mutant prevention concentration (MPC) test and the minimum inhibitory concentration (MIC) test, in which the result was the ethanol extract of white pumpkin leaves with 0,5% concentration could prevent 4 pathogen bacteria which was obtained from screening test 2 % concentrationagainst extract of white pumpkin leaves that are able to kill 4 pathogen bacteria. Another test was performed with inhibitory test through agar diffusion method so that some blocking pathogen bacteria to screening result (Escherichia Coli, Streptococcus mutants, Staphylococcus Aurous, and Staphylococcus Epidermidises) against 0,5%, 1% and 2 % concentration. Moreover the chloramphenicol is as positive control. The result which was obtained respectively was the biggest obstacle zone diameter towards Escherichia coli, Streptococcus mutants, Staphylococcus aureus, and Staphylococcus epidermidis bacteria were 2,2 cm; 4,1 cm; 2,43 cm and 3,73 cm.